The Effect of Ethambutol on Optic Nerve by Spectral Domain Optical Coherence Tomography - Gül VARAN; Ahmet ŞAHİN (Namık Kemal Tıp Dergisi, 2020)

(untitled)
Aim:To evaluate; the retinal nerve fiber layer difference between healthy control groups and patients who were taking ethambutol medication by using spectral domain optical coherence tomography (SD-OCT) and to evaluate the usage of SD-OCT for early diagnosis of optic neuropathy due to ethambutol.Materials and Methods:40 eyes of 20 patients using ethambutol for at least 2 months have been compared to 40 eyes of 20 healthy subjects of the same age and sex in terms of RNFL thickness parameters. All participants underwent a complete ophthalmologic examination. Patients with a history of disease or drug use affecting RNFL were not included in the study. Superior, inferior, nasal and temporal quadrants and macular thickness were evaluated in SD-OCT.Results:RNFL thickness values of ethambutol patients were as follows: superior 123,12±16,07μm, inferior 131,20±13,26 μm, nazal 79,47±11,54 μm, temporal 78,80±12,82 μm, macular thickness 266,16±11,94 μm.Conclusion:There was statistically significant increase in temporal quadrant and decrease in nasal quadrant in patients taking ethambutol medication compared to control group (p<0,05). There was no statistically significant change in superior and inferior quadrant and macular thickness (p>0,05).